(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2023)
Antonin Artaud, words, drawings, and the extreme and traumatic condition of an individual who pushed back the boundaries of history, of his own time, in Europe’s darkest days. Such is my scope in the pages that follow. This essay examines the drawings produced by Artaud between 1944 and 1946. They offer a particularly helpful starting point for a series of reflections on, on the one hand, a concept of identity that had emerged and re-emerged with a new critical awareness following the close of the Second World War, and on the other, how – leaving behind a modernism in which the cracks were clearly showing – it is from madness and suffering that the contemporary notion of the individual is reborn.